Hubungan Beban Kerja Perawat Instalasi Gawat Darurat Dengan Kepatuhan Pelaksaan Standar Prosedur Operasional Penerimaan Pasien Baru di RSU GMIM Pancaran Kasih Kota Manado - Rahmawati Inggrit Yunus; Silvia Dewi Mayasari Riu; Irma M. Yahya (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Workload is a description of the volume of work. In hospitals, the workload covers many aspects and this has an impact on compliance with the implementation of SOPs for new patient admissions which can be influenced by high workloads. The aim of this research is to determine